2019
DOI: 10.3389/fimmu.2019.01004
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 Involvement in Chemical-Induced Skin Innate Immunity

Abstract: Exposure to certain chemicals disturbs skin homeostasis. In particular, protein-reactive chemical contact sensitizers trigger an inflammatory immune response resulting in eczema and allergic contact dermatitis. Chemical sensitizers activate innate immune cells which orchestrate the skin immune response. This involves oxidative and inflammatory pathways. In parallel, the Nrf2/Keap1 pathway, a major ubiquitous regulator of cellular oxidative and electrophilic stress is activated in the different skin innate immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 120 publications
0
57
0
Order By: Relevance
“…Recent studies have demonstrated that the NRF2 pathway is implicated in both inflammatory and oxidative stress responses [ 36 ], and its modulation may be effective for managing inflammatory diseases, including dermatitis [ 37 , 38 , 39 ]. Several chemicals that can stimulate NRF2 expression have been tested for their application as therapeutic agents for RD [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated that the NRF2 pathway is implicated in both inflammatory and oxidative stress responses [ 36 ], and its modulation may be effective for managing inflammatory diseases, including dermatitis [ 37 , 38 , 39 ]. Several chemicals that can stimulate NRF2 expression have been tested for their application as therapeutic agents for RD [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that PTNs effectively suppress or delay the acute inflammatory response in the early phase of RD. Crosstalk occurs between the NRF2 and NF-κB pathways: NRF2 signaling inhibits the NF-κB pathway and vice versa [ 36 , 37 ]. Thus, PTNs may suppress the radiation-induced NF-κB pathway via NRF2 activation, thereby reducing the RD scores.…”
Section: Discussionmentioning
confidence: 99%
“…In normal physiological conditions, Nrf2 exists as an inactive complex with the negative regulator called Kelch-like-ECH-associated protein 1 (Keap1): a 624 amino acid, cysteine-rich, homodimeric zinc-finger protein [195]. In fact, Keap1 is responsible for forwarding Nrf2 to a Cul3-based E3 ligase with the following rapid 26S proteasome degradation with a half-life under physiological conditions of only ∼20 min [196,197]. Importantly, more than 27 cysteine residues possessing different reactivity and having various functional impact on Nrf2 were identified in Keap1.…”
Section: Transcription Factor Nrf2mentioning
confidence: 99%
“…Table 3. Principal functions of enzymes encoded by Nrf2 target genes and involved in the antioxidant defence [186,197,[202][203][204].…”
Section: Transcription Factor Nrf2mentioning
confidence: 99%
See 1 more Smart Citation